2007
DOI: 10.1002/ejoc.200601022
|View full text |Cite
|
Sign up to set email alerts
|

Meroterpenoid Pigments from Albatrellus flettii (Basidiomycetes)

Abstract: Keywords: Natural products / Meroterpenoids / Mushrooms / Quinones / FuransThe pigments responsible for the blue colour of the North American polypore Albatrellus flettii have been isolated and their structures elucidated by spectroscopic methods. Albatrellin, a dimeric meroterpenoid with a furylbenzoquinone chromophore, is accompanied by its 16-hydroxy and 16-oxo derivatives. The latter has recently been described as grifolone B from a Japanese collection of A. caeruleoporus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Since the NMR spectroscopic data exclude a connection of partial structure A with the aromatic part of the molecule through one of the 4‐hydroxyphenyl rings, the second half of cristatomentin is represented by structure B (Figure 1). A combination of both partial structures yields constitution 5 for cristatomentin, which is supported by the agreement of the chemical shift values for the carbon atoms connecting both moieties in cristatomentin ( 5 ) (C‐6: δ C = 134.3 ppm; C‐21′: δ C = 141.3 ppm) and albatrellin ( 6 ) (C‐6: δ C = 135.5 ppm; C‐21′: δ C = 140.3 ppm) 6a…”
Section: Comparison Of the 1h And 13c Nmr Spectroscopic Data For The supporting
confidence: 57%
See 2 more Smart Citations
“…Since the NMR spectroscopic data exclude a connection of partial structure A with the aromatic part of the molecule through one of the 4‐hydroxyphenyl rings, the second half of cristatomentin is represented by structure B (Figure 1). A combination of both partial structures yields constitution 5 for cristatomentin, which is supported by the agreement of the chemical shift values for the carbon atoms connecting both moieties in cristatomentin ( 5 ) (C‐6: δ C = 134.3 ppm; C‐21′: δ C = 141.3 ppm) and albatrellin ( 6 ) (C‐6: δ C = 135.5 ppm; C‐21′: δ C = 140.3 ppm) 6a…”
Section: Comparison Of the 1h And 13c Nmr Spectroscopic Data For The supporting
confidence: 57%
“…The EI‐MS of cristatomentin ( 5 ) shows that the compound suffers thermal decarboxylation2a,6a and yields a pseudo molecular ion peak at m / z (%) = 646 (4) in additionto a more intense peak at m / z (%) = 648 (16); [M + 2] ions are characteristic for benzoquinones and arise by reduction of the quinone in the inlet system 8. Two fragment ions at m / z (%) = 340 (10) [C 22 H 28 O 3 ] and 310 (100) [C 18 H 14 O 5 ] correspond to the molecular compositions of cristatin ( 2 ) and 2‐deoxyleucoatromentin ( 10 ), respectively, and indicate thermal cleavage of decarboxyleucocristatomentin ( 7 ; m / z = 648) in the inlet system (Scheme ).…”
Section: Comparison Of the 1h And 13c Nmr Spectroscopic Data For The mentioning
confidence: 99%
See 1 more Smart Citation
“…An intensive [M + H] + ion peak in the EIMS spectrum, a strong IR absorption at 1647 cm −1 , and two downfield carbon signals at δ C 184.1 and 186.9 were characteristic for a quinone moiety. 9 Further, The HMBC cross-peaks from H-7′ (δ H 3.17) to C-2′, C-6′, and C-1′ and from OH-2′ to C-1′, C-3′, and C-2′ revealed that 5a was a pbenzoquinone with a farnesyl group at position 1′. Me-22′ was located at position 4′ based on the HMBC cross-peaks from Me-22′ to C-3′, C-4′, and C-5′ ( Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…142 The pigments albatrelin 288 and 16hydroxyalbatrelin 289, responsible for the blue color of A. flettii, have been isolated and their structure elucidated by spectroscopic methods. 143 288 is a dimeric meroterpenoid with a furylbenzoquinone chromophore. In addition, grifolinone C 290, which displays an alternative mode of dimerisation through the aromatic moieties, was obtained from the fruiting bodies of A. confluens, accompanied by 274, 275, 287, and 288.…”
Section: Derived From Other Tetraketidesmentioning
confidence: 99%